Humeral lengthening: a report of 2 cases - Netrawichien P. (2014)
Surgical lengthening of the humerus can be performed safely if the surgeon takes care to avoid and prevent complications which may occur. The technic depends on the surgeon's experience, but preservation of the periosteal and endoosteal blood supply should be of concern. The amount of lengthening less than 10 cm is safe. Bone graft is not necessary when Ilizarov's concept is used.